2020
DOI: 10.7759/cureus.10768
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Intravenous Dexmedetomidine Sedation With Perineural Dexmedetomidine on Supraclavicular Approach Brachial Plexus Block in Upper Limb Orthopaedic Surgery

Abstract: Background Dexmedetomidine is being used as an adjuvant analgesic, both as intravenous (IV) and intrathecal infusion. The role of perineural (P) dexmedetomidine has evoked attention recently. The aim of this study was to compare the effect of IV dexmedetomidine and P dexmedetomidine as an adjunct to supraclavicular brachial plexus block in upper limb orthopaedic surgery. Methods Patients were randomly divided into two equal groups (n=20). Group I (IV dexmedetomidine) received d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Sehmbi et al 55 showed that intravenous dexmedetomidine infusion did not prolong the sensation, motor, or pain relief duration. Samar et al 56 revealed that intravenous dexmedetomidine could produce sensory block earlier, with a longer sensory and motor block and analgesia duration. Regarding the onset and duration of block and duration of analgesia, Somsunder et al 57 discovered that intravenous dexmedetomidine was equally effective as epineural dexmedetomidine, but the hemodynamic fluctuation was larger.…”
Section: Application Of Dexmedetomidine In Peripheral Nerve Blockmentioning
confidence: 99%
“…Sehmbi et al 55 showed that intravenous dexmedetomidine infusion did not prolong the sensation, motor, or pain relief duration. Samar et al 56 revealed that intravenous dexmedetomidine could produce sensory block earlier, with a longer sensory and motor block and analgesia duration. Regarding the onset and duration of block and duration of analgesia, Somsunder et al 57 discovered that intravenous dexmedetomidine was equally effective as epineural dexmedetomidine, but the hemodynamic fluctuation was larger.…”
Section: Application Of Dexmedetomidine In Peripheral Nerve Blockmentioning
confidence: 99%
“…Upper limb surgery is often performed under brachial plexus block (BPB), which is a series of regional anesthesia techniques and also contributes to reliable postoperative analgesia [ 1 ]. Single block and continuous catheter-based block are two different anesthesia regimens.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, respiratory suppression induced by DEX is lesser than that induced by other sedation agents [11]. There are also two reports that the combined use of DEX with local anaesthesia prolonged the effect of the local anaesthetic [12,13]. Although it is not a common method of administration and is still in the research stage, there is a report that DEX administered into the subarachnoid region of the spinal cord produced a mild sedative effect while enhancing the effects of spinal anaesthesia [14].…”
Section: Discussionmentioning
confidence: 99%